2021
DOI: 10.4103/jcar.jcar_26_20
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival outcome of breast cancer patients in India

Abstract: INTRODUCTION: Breast cancer is the most frequently diagnosed cancer among women in India; however, there are no studies addressing long-term survival (10 years and above). This study sought to evaluate long-term oncological outcome among women with breast cancer treated with a curative intent. MATERIALS AND METHODS: This is a retrospective cohort analysis of 1301 breast cancer patients of all stages who had received primary treatment with curative intent from 2004 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to the American Cancer Society, breast cancer survival rates in the United States are relatively high, with a 91% survival rate at 5 years postdiagnosis and 84% at 10 years. 13 In contrast, a study by Viral et al 14 in India reported a 5-year OS of 79% and a 10-year breast cancerspecific survival of 70%. Another Indian study by Doval et al, 15 which included only early operable breast cancer patients, found a 5-year OS of 94.1% and a disease-free survival (DFS) of 88.1%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the American Cancer Society, breast cancer survival rates in the United States are relatively high, with a 91% survival rate at 5 years postdiagnosis and 84% at 10 years. 13 In contrast, a study by Viral et al 14 in India reported a 5-year OS of 79% and a 10-year breast cancerspecific survival of 70%. Another Indian study by Doval et al, 15 which included only early operable breast cancer patients, found a 5-year OS of 94.1% and a disease-free survival (DFS) of 88.1%.…”
Section: Discussionmentioning
confidence: 94%
“…Four hundred and sixteen patients (62.93%) had angiolymphatic invasion and 119 patients (18.00%) had perineural invasion. Median Ki67% was 40%, median number of nodes dissected were 14, [10][11][12][13][14][15][16][17][18][19] and median number of positive nodes were 4. 2-7,20…”
Section: Treatment Characteristicsmentioning
confidence: 99%
“…BC seems to be the cause of 18.2% of all cancer deaths, 16.2% of all female cancers, and 22.9% of invasive cancers [4]. Despite extensive research on the underlying processes of BC initiation and progression, patients suffering from BC are still facing high mortality rates [5,6]. BC is generated by a wide range of molecular alterations which makes it a highly polymorphic disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic reviews [ 4 7 ] indicate that regular screening mammography can increase the early detection of breast pre-malignancies or malignancies and reduce the risk of late-stage breast cancer, decreasing breast cancer-specific morbidity and mortality. Thus, the ten-year breast cancer-specific survival rate is reported more than 70% in recent studies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%